2022
DOI: 10.1186/s12904-022-00948-x
|View full text |Cite
|
Sign up to set email alerts
|

“I want to get myself as fit as I can and not die just yet” – Perceptions of exercise in people with advanced cancer and cachexia: a qualitative study

Abstract: Cachexia is a prevalent muscle wasting syndrome among people with advanced cancer that profoundly impacts patient quality of life (QoL) and physical function. Exercise can improve QoL, physical function, and overall health in people with cancer and may be an important addition to treatment approaches for cancer cachexia. Greater understanding of patients’ perception of exercise can help elucidate the feasibility of implementing exercise interventions for cancer cachexia and facilitate the design of patient-cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Bland et al's qualitative study (2022) focused on how people with advanced cancer and cachexia perceive exercise and identified barriers that keep them from exercising, such as, for example, fatigue. They concluded that cancer patients should get offered a combination of home-based and supervised options for exercise: "Combining unsupervised home-based with supervised exercise, which may include incorporating telehealth, may help balance patient exercise preferences that we identified in the current study" (45).…”
Section: Discussionmentioning
confidence: 97%
“…Bland et al's qualitative study (2022) focused on how people with advanced cancer and cachexia perceive exercise and identified barriers that keep them from exercising, such as, for example, fatigue. They concluded that cancer patients should get offered a combination of home-based and supervised options for exercise: "Combining unsupervised home-based with supervised exercise, which may include incorporating telehealth, may help balance patient exercise preferences that we identified in the current study" (45).…”
Section: Discussionmentioning
confidence: 97%
“…However, the possibility to exercise seemed to be limited by disease- and treatment-related physical constraints and resulting insecurities about the appropriate exercise type, amount, and execution. Insecurities and fear have been previously reported as exercise barriers in diverse cancer populations [ 21 , 23 , 40 ], but could be even more prominent for MBC patients given the adverse effects of their typically longer treatment history, having metastases and especially the (potential) presence of bone metastases. This could also explain women’s strong wish for professional supervision when exercising.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure exercise safety and effectiveness, instruction by a trained professional is advisable [ 19 , 20 ], while the content of an exercise program can be designed according to patients’ perceived barriers, facilitators, and preferences to improve exercise adherence. Previous research on this topic has largely been limited to early-stage breast cancer patients [ 21 , 22 ] or mixed cancer types [ 23 26 ], whose needs and preferences may differ from those of patients with MBC [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 86% adherence of our study is among the highest reported for a lifestyle intervention for endometrial cancer patients. Our high attendance rates may be explained by our individualized one-to-one sessions and the accessibility of a local gym, as they are known factors to improve exercise engagement and overcome barriers [ 17 , 38 ]. Studies by Rossi et al and Koutoukidis et al evaluating face to face interventions delivered through group sessions have reported rates of 60 to 77% [ 31 , 35 ].…”
Section: Discussionmentioning
confidence: 99%